Efeito de fungicidas no processo infeccioso de Phakopsora pachyrhisi - Zanatta, Tiago (2010)
Soybean crop occupies one of the most important highlights in the scenario of Brazilian agribusiness and in the world. The diseases are among the main causes of the reduction of grain yield. From 2000/01 the asian soybean rust has become the main disease of the crop in Brazil. Countless work has been done to develop resistant cultivars. However, with no success. For this reason, until now, the main control measure of the disease is the use of fungicides application above found organs. In recent years, much has been discussed about the effect of fungicide in preventive, curative and eradicative application. Furthermore, although many studies have been conducted evaluating the effect of fungicides in the control of asian soybean rust, the results are still limited to only certain fungicides, and only a little information available concerning the major fungicides used at this time. The objective of this study was to evaluate the effect of triazole fungicides and mixtures of triazoles + strobilurins in preventive, curative application (latent infections), and the eradicative effect on uredia and spores. Fungicides chlorothalonil, flutriafol, tebuconazole, cyproconazole + trifloxystrobin, epoxiconazole + pyraclostrobin, cyproconazole + azoxystrobin and cyproconazole + picoxystrobin were evaluated. Initially, in growth chamber the effect of adjuvant polyoxyethylene sorbitane monolaurate (Tween 20%) in concentrations of 0, 30, 60, 120, 240, 480 and 960 μL.L-1 and a fixed concentration of 2 x 104 uredospores.mL-1 were evaluated. In the second phase the following concentrations 0, 5 x 103, 1 x 104, 2 x 104, 4 x 104, 8 x 104, and 16 x 104 uredospores.mL-1 and the concentration of the spreader in 240 μL.L-1, selected in the previous experiment were tested. The curative and eradicative fungicides effect were evaluated after inoculation of the concentration of 5 x 103 uredosporos.mL-1 with the addition of adjuvant 240 μL.L-1 of water. And finally, in the field, protection period and eradicative effect of fungicides in the control of asian soybean rust were assessed. It was determined that the best concentration of adjuvant was 240 μL.L-1 of water, and the best concentration of uredospores was 4 x 104.mL-1, however, it was used the concentration of 5 x 103 uredosporos.mL-1. Finally, the period of protection of fungicides flutriafol, tebuconazole and cyproconazole + trifloxystrobin was 14 days, and 25 days for fungicides epoxiconazole + pyraclostrobin, cyproconazole + azoxystrobin and cyproconazole + picoxystrobin. The eradicative effect of fungicides in the first season was higher for mixtures of fungicides and in the second season there was no difference